2015
DOI: 10.1016/j.enconman.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Part-load performance of a high temperature Kalina cycle

Abstract: The Kalina cycle has recently seen increased interest as an alternative to the conventional steam Rankine cycle. The cycle has been studied for use with both low and high temperature applications such as geothermal power plants, ocean thermal energy conversion, waste heat recovery, gas turbine bottoming cycle and solar power plants. The high temperature cycle layouts are inherently more complex than the low temperature layouts due to the presence of a distillation-condensation subsystem, three pressure levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The results indicated that the highest rate of exergy destruction in the power cycle occurs in the receiver/boiler. The study was continued with a full thermoeconomic optimization [114,119] with the minimization of LCOE as the objective function by combining the detailed thermodynamic design [115] and the part-load models [116] in order to evaluate the cycle performance over a year. The results suggested that a Kalina cycle power system without storage cannot compete with the state-of-the-art steam Rankine cycle power system for high temperature solar power applications when considering both the thermodynamic and the economic aspects.…”
Section: Solar Energy Based Kalina Cycle Power Systemsmentioning
confidence: 99%
“…The results indicated that the highest rate of exergy destruction in the power cycle occurs in the receiver/boiler. The study was continued with a full thermoeconomic optimization [114,119] with the minimization of LCOE as the objective function by combining the detailed thermodynamic design [115] and the part-load models [116] in order to evaluate the cycle performance over a year. The results suggested that a Kalina cycle power system without storage cannot compete with the state-of-the-art steam Rankine cycle power system for high temperature solar power applications when considering both the thermodynamic and the economic aspects.…”
Section: Solar Energy Based Kalina Cycle Power Systemsmentioning
confidence: 99%
“…A methodology to obtain the nominal operating condition for the Kalina cycle KC12 was presented in detail by Modi et al [26]. The validation of the general solution algorithm for the high temperature Kalina cycles was also presented [26]. The following assumptions were made for the thermodynamic design of the Kalina cycle CSP plant [25,35].…”
Section: Kalina Cyclementioning
confidence: 99%
“…3. In general, the following steps were used to solve the Kalina cycle for each iteration of the optimization process [26]. The turbine TUR was solved first to obtain the state at the turbine outlet.…”
Section: Kalina Cyclementioning
confidence: 99%
See 2 more Smart Citations